KONDISI PAELOSALINITAS PADA MIOSEN AKHIR–PLEISTOSEN DI CEKUNGAN JAWA TIMUR UTARA, INDONESIA, BERDASARKAN PERUBAHAN POPULASI NANOPLANKTON - Wahyu Dwijo Santoso; Halmi Insani; Rubiyanto Kapid (Indonesian Institute of Sciences, 2014)
Abstract Quantitative biostratigraphy analysis by observing Sphenolithus abies and Helicosphaera carteri could predict paleosalinity changes at a sedimentary basin diachronically. Hyposaline conditions can be investigated from the abundance changes of Helicosphaera carteri and Calcidiscus leptoporus counts. Along this line, the increasing number of Sphenolithus abies demonstrates particular states of normal saline. Paleosalinity changes in the North East Java Basin, from Late Miocene to Pleistocene were identified from the top of Wonocolo Formation to bottom of Ledok Formation. Paleosalinity along this episode was interpreted as hyposaline condition. While at the top of Ledok Formation to Mundu Formation; paleosalinity had changed to normal saline. Furthermore, environmental conditions return to hyposaline when Selorejo Formation sediment was deposited. And during the deposition of Lidah Formation, deposition environment had returned to the normal saline.